The Spatio-temporal Distribution of Japanese Encephalitis Cases in Different Age Groups in Mainland China, 2004 - 2014. - Xiaolong Li; Shiheng Cui; Xiaoyan Gao; Huanyu Wang; Miao Song; Minghua Li; Shihong Fu; Zhi Lv; Ying He; Wenwen Lei; Bin Wang; Xiaoqing Lu; et al. (Public Library of Science (PLoS), 2016)
Japanese encephalitis (JE) is very prevalent in China, but the incidence of JE among children has been greatly reduced by extensive promotion of vaccinations. The incidence of JE among adults, however, has increased in some parts of China.Data on JE in mainland China, in terms of incidence, gender, and age, were collected between 2004 and 2014. We conducted spatial and temporal analyses on data from different age groups. Generally, children aged 0-15 years still represent the major population of JE cases in China, despite the gradual decrease in incidence over years. However, the incidence of JE among adults in several provinces is notably higher than the national average, especially during the epidemic waves in 2006, 2009, and 2013. The JE cases in the 0-15-year-old group are distributed mainly in the area south of the Yangtze River, with peak incidence occurring from July to September. In the adult group, especially for those over 40 years old, the JE cases are concentrated mainly in the area north of the Yangtze River. JE incidence in the adult group in September and October is significantly greater compared to the other groups. Further analysis using Local Indicators of Spatial Association (LISA) reveals that the distribution of adult JE cases in the six provinces north of the Yangtze River, between north 30-35° latitude and east 110-130° longitude, is a hotspot for adult JE cases.The rate of JE case increase for adults is much greater than for children and has become a public health issue. Therefore, studies on the necessity and feasibility of vaccinating adults who live in JE-endemic areas, but have never been vaccinated for JE, should become a new focus of JE prevention in the future.